THE RESPONSE OF PER1 TO LIGHT IN THE SUPRACHIASMATIC NUCLEUS OF THE DIURNAL DEGU (OCTODON DEGUS) - Koch, Jessica M. (2009)
Several studies suggest that the circadian systems of diurnal mammals respond differently to daytime light than those of nocturnal mammals. We hypothesized that the photosensitive “clock” gene Per1 would respond to light exposure during subjective day in the suprachiasmatic nucleus of the diurnal rodent, Octodon degus. Tissue was collected 1.5–2 h after a 30 min light pulse presented at five timepoints across the 24 h day and compared to controls maintained under conditions of constant darkness. Per1 mRNA was quantified using in situ hybridization. Results showed that the rhythmicity and photic responsiveness of Per1 in the degu resembles that of nocturnal animals.